Mapping genres, mapping culture : Japanese texts in context - Thomson, Elizabeth A. (Elizabeth Anne), 1961-; Sano, Motoki, 1980-; De Silva Joyce, Helen (Pragmatics & beyond, 2017)
The purpose of this book is to contribute to our understanding of genre and genre variation in the Japanese language in order to bring to consciousness the nature of Japanese culture and the presuppositions, norms and values found within Japanese society. This type of knowledge enables interventions and agency, as knowing how language works within a culture makes it possible to consciously accept it or to influence and shape it into the future. The various chapters seek to explore social contexts and the norms, values and practices of Japanese culture through the language choices in analysed texts in literature, education, the workplace and in print-based media. These genres collectively form part of the cultural fabric of Japan. The book represents a first step in documenting a selected set of Japanese genres from a social semiotic perspective. It will be of interest to students and scholars in a wide range of linguistic fields, such as Japanese descriptive linguistics, pragmatics, sociolinguistics, discourse analysis, systemic functional linguistics and applied linguistics. It should also appeal to teachers and learners of Japanese and to media commentators, students of literature, cultural studies and journalism.